Strategic thinkers and their characteristics: Toward a multimethod typology development - Katarzyna Piórkowska; Anna Witek-Crabb; Janusz M. Lichtarski; Maciej Wilczyński; Sylwia Wrona (International Journal of Management and Economics, 2021)
We aimed to explore the strategic thinking concept by searching for differences within the population of strategic thinkers to contribute to the development of the "strategic thinking" concept. To answer the research questions and achieve the research aim, we implemented the following research methods: a systematic literature review and biographical studies. (1) As the first stage in researching strategic thinking, the qualitative approach is recommended. (2) The main features of strategic thinkers are a strategic perspective and a reflective style of thinking. (3) Two groups of differentiating features have been identified: features concerning the content of strategic thinking; and features concerning the process of strategic thinking. Most academic research on strategic thinkers concentrates on the common characteristics and similarities, while little attention has been paid to features that internally differentiate the population of strategic thinkers. Our main contribution to the literature is filling this knowledge gap.
Keywords: D22; L2; 650; biographical method; strategic thinkers; strategic thinking; systematic literature review